Профессиональный стандарт как модель деятельности специалиста библиотечно-информационной сферы (Библиосфера, 2010)
Inconsistency of professional regulations is characterized and the content analysis of job instructions is given. The possibility of introducing professional standards in the library and information activity as the basis for developing educational standards and job descriptions. An example of a professional standard of the fifth professional qualification level is given.